2012
DOI: 10.1074/jbc.c111.279927
|View full text |Cite
|
Sign up to set email alerts
|

Action of Protein Disulfide Isomerase on Proinsulin Exit from Endoplasmic Reticulum of Pancreatic β-Cells

Abstract: Background:We have examined the effect of PDI knockdown in pancreatic ␤-cells. Results: Upon knockdown, proinsulin oxidation to form native disulfide bonds is enhanced and accompanied by improved exit from the ER with increased total insulin secretion. Conclusion:We hypothesize that PDI exhibits unfoldase activity for proinsulin. Significance: Unexpectedly, PDI increases retention of proinsulin within the ER of pancreatic ␤-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 23 publications
5
55
0
1
Order By: Relevance
“…Conditions that adversely affect ER export of proinsulin, including dysregulated mRNA translation, impaired ER-to-Golgi traffic (3,4), or alteration of the ER environment that impairs rate/efficiency of proinsulin monomer folding (5,6) promote insulin deficiency and glucose intolerance. Conversely, enhanced exit from the ER is correlated with increased protein entry into forming granules, (7) which, in ␤ cells, increases insulin production (8). These findings seem to imply that proinsulin egress from the ER is rate-limiting for insulin production.…”
mentioning
confidence: 54%
“…Conditions that adversely affect ER export of proinsulin, including dysregulated mRNA translation, impaired ER-to-Golgi traffic (3,4), or alteration of the ER environment that impairs rate/efficiency of proinsulin monomer folding (5,6) promote insulin deficiency and glucose intolerance. Conversely, enhanced exit from the ER is correlated with increased protein entry into forming granules, (7) which, in ␤ cells, increases insulin production (8). These findings seem to imply that proinsulin egress from the ER is rate-limiting for insulin production.…”
mentioning
confidence: 54%
“…The notion that rather than prevent, the formation of proAVP aggregates or polymers. Given our own data and the current literature (3,33,56), we propose 2 possible modes of action for PDI in the context of proAVP ERAD, as illustrated in Figure 9C. PDI may act to reduce and unfold proAVP targeted for ERAD, which may result in the generation of unfolded substrates with highly reactive cysteine thiols.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that PDI subserves a pro-folding role in WT cells (30,55), and more recently, studies have demonstrated that PDI, but not other members of the PDI family (ERp57 and ERdj5), may also participate in ERAD by feeding reduced protein substrates (e.g., Akita proinsulin and thyroglobulin) to the ERAD machinery (3,33,56 (20). Single-guide RNA (sgRNA) oligonucleotides were designed for human HRD1 (5′-GGA-CAAAGGCCTGGATGTAC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29] Likewise, the unfolded protein response induced by NO could be also due to the regulation of protein disulfide isomerases (PDIA6 and P4HB (PDIA1) in HPI improving the protein folding including insulin for its accurate secretion. 30 Increments in ATP5A1, P4HB and HSPA8 and other proteins such as HSPD1, ATP6V1B1 and HSP90B1 were also detected in NO-treated, serum-deprived mouse pancreatic islets when compared with islets cultured under serum withdrawal, despite having used a different strategy for analyzing the spots (Table S1 and Figure S1). It is also relevant to note the existence of species differences in keratin expression.…”
Section: Discussionmentioning
confidence: 99%